PENGARUH DEBT TO ASSET RATIO, NET PROFIT MARGIN, DAN EARNING PER SHARE TERHADAP RETURN SAHAM (Studi Empiris Pada Perusahaan Makanan dan Minuman yang Terdaftar di BEI Periode 2020-2023) - Rahman, Sandy Fathur; Cahyono, Yuli Tri (widya balina, 2024)
This study aims to determine and analyze the effect of debt to asset ratio, net profit margin, and earning per share on stock returns. This type of research is quantitative research. The population in this study is the report data of food and beverage companies listed on the BEI as many as 48 companies as samples. Data analysis using multiple linear regression analysis. From the results of data analysis show that debt to asset ratio affects stock returns, while net profit margin and earning per share have no effect on stock returns. The results of this study are expected to be taken into consideration for evaluation in decision making, as well as reference material for further research.